Trade-offs and synergies in the management of environmental pressures: a case study on ship noise mitigation - Karen de Jong; Cathryn C. Murray; Asier Anabitarte; Sarah Bailey; Lisa Drake; Jose A. Fernandes-Salvador; Ida-Maja Hassellov; Nicole Heibeck; Jukka-Pekka Jalkanen; Annukka Lehikoinen; Nathan Merchant; Amanda T. Nylund; et al. (Marine Pollution Bulletin, 2025)

Harbour porpoises respond to chronic acoustic deterrent device noise from aquaculture - Charlotte R. Findlay; Frazer G. Coomber; Rebecca Dudley; Lynsey Bland; Susannah V. Calderan; Lauren Hartny-Mills; Russell Leaper; Jakob Tougaard; Nathan D. Merchant; Denise Risch; Ben Wilson (Biological Conservation, 2024)

Vessel noise prior to pile driving at offshore windfarm sites deters harbour porpoises from potential injury zones - Aude Benhemma-Le Gall; Paul Thompson; Nathan Merchant; Isla Graham (Environmental Impact Assessment Review, 2023)

Broad-Scale Responses of Harbor Porpoises to Pile-Driving and Vessel Activities During Offshore Windfarm Construction - Aude Benhemma-Le Gall; Isla M. Graham; Nathan D. Merchant; Paul M. Thompson (Frontiers in Marine Science, 2021)
Offshore windfarm developments are expanding, requiring assessment and mitigation of impacts on protected species. Typically, assessments of impacts on marine mammals have focused on pile-driving, as intense impulsive noise elicits adverse behavioral responses. However, other construction activities such as jacket and turbine installation also change acoustic habitats through increased vessel activity. To date, the contribution of construction-related vessel activity in shaping marine mammal behavioral responses at windfarm construction sites has been overlooked and no guidelines or mitigation measures have been implemented. We compared broad-scale spatio-temporal variation in harbor porpoise occurrence and foraging activity between baseline periods and different construction phases at two Scottish offshore windfarms. Following a Before-After Control-Impact design, arrays of echolocation click detectors (CPODs) were deployed in 25 km by 25 km impact and reference blocks throughout the 2017–2019 construction. Echolocation clicks and buzzes were used to investigate porpoise occurrence and foraging activity, respectively. In parallel, we characterized broadband noise levels using calibrated noise recorders (SoundTraps and SM2Ms) and vessel activities using AIS data integrated with engineering records. Following an impact gradient design, we then quantified the magnitude of porpoise responses in relation to changes in the acoustic environment and vessel activity. Compared to baseline, an 8–17% decline in porpoise occurrence was observed in the impact block during pile-driving and other construction activities. The probability of detecting porpoises and buzzing activity was positively related to the distance from vessel and construction activities, and negatively related to levels of vessel intensity and background noise. Porpoise displacement was observed at up to 12 km from pile-driving activities and up to 4 km from construction vessels. This evidence of broad-scale behavioral responses of harbor porpoises to these different construction activities highlights the importance of assessing and managing all vessel activities at offshore windfarm sites to minimize potential impacts of anthropogenic noise.

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Vessel noise cuts down communication space for vocalizing fish and marine mammals - Rosalyn L. Putland; Nathan D. Merchant; Adrian Farcas; Craig A. Radford (Global Change Biology, 2018)
Anthropogenic noise across the world's oceans threatens the ability of vocalizing marine species to communicate. Some species vocalize at key life stages or whilst foraging, and disruption to the acoustic habitat at these times could lead to adverse consequences at the population level. To investigate the risk of these impacts, we investigated the effect of vessel noise on the communication space of the Bryde's whale Balaenoptera edeni , an endangered species which vocalizes at low frequencies, and bigeye Pempheris adspersa , a nocturnal fish species which uses contact calls to maintain group cohesion while foraging. By combining long‐term acoustic monitoring data with AIS vessel‐tracking data and acoustic propagation modelling, the impact of vessel noise on their communication space was determined. Routine vessel passages cut down communication space by up to 61.5% for bigeyes and 87.4% for Bryde's whales. This influence of vessel noise on communication space exceeded natural variability for between 3.9 and 18.9% of the monitoring period. Additionally, during the closest point of approach of a large commercial vessel,

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Underwater Ambient Noise in a Baleen Whale Migratory Habitat Off the Azores - Miriam Romagosa; Irma Cascão; Nathan D. Merchant; Marc O. Lammers; Eva Giacomello; Tiago A. Marques; Mónica A. Silva (Frontiers in Marine Science, 2017)